Couples' Time Together: Complementarities in Production versus Complementarities in Consumption - Hani Mansour; Terra McKinnish (Institute for the Study of Labor (IZA), 2013)
Economists have previously suggested that gains from marriage can be generated by complementarities in production (gains from specialization and exchange) or by complementarities in consumption (gains from joint consumption of household public goods and joint time consumption). This paper uses the American Time Use Survey (ATUS) from 2003-2011 to test whether couples that engage in less specialization (are more similar in hours of market work) spend more time together. We find that among married couples without young children, those with a greater difference in weekly hours of work between husband and wife spend less time together on non-working weekend days. Importantly, we find that this relationship is quite symmetric between couples in which the husband works greater hours and couples in which the wife works greater hours. We do not find evidence of a relationship between specialization and couple time together among couples with young children.
Keywords: J12; J13; J16; 330; time use; home production; joint consumption